“A second birthday”? Experiences of persons with multiple sclerosis treated with autologous hematopoietic stem cell transplantation—a qualitative interview study - Volz, Timo; Sippel, Anna; Fischbach, Felix; Richter, Johanna; Willison, Alice Grizzel; Häußler, Vivien; Heesen, Christoph (Frontiers in Neurology, 2024)
Introduction and objective Autologous hematopoietic stem cell transplantation (aHSCT) is a promising treatment option for persons with multiple sclerosis (pwMS). Patients undergoing aHSCT face unique challenges in all aspects of life. In this study, we explored the lived experiences of pwMS undergoing aHSCT. Methods Semi-structured interviews of 12 pwMS treated with aHSCT were conducted using a maximum variation sampling strategy. Interviews were transcribed verbatim and analyzed thematically using inductive and deductive categories. Results Three major themes were identified: (1) preparing for aHSCT, (2) experiencing the procedure, and (3) post-treatment time. A difficult decision-making process, organizational effort, and funding difficulties characterized the preparation for transplantation. AHSCT was seen as a life-changing event accompanied by both psychological and physical stress, with an associated feeling of regaining control. The transplantation had a lasting positive effect on the lives of the interviewed pwMS. However, the early post-treatment time was characterized by successes and failures alike. Particularly the independently organized medical aftercare was perceived as challenging. Retrospective revaluation has led most pwMS to wish for earlier information provision about the treatment option of aHSCT during their treatment history. Conclusion AHSCT had a clear impact on patients’ physical and psycho-social health, influencing their perception of life and its quality. Assessing and attending to unmet needs of patients before, during, and after transplantation may positively influence their experience of aHSCT.